SME Solutions Center—Kenya : Developing Alternative Financing Solutions for Small and Medium Enterprises - Maina, Kiragu; Butoyi, Scholastica; Michira, Nkatha (World Bank, Washington, DC, 2012)
Small and medium enterprises (SMEs) in Africa have been hailed as the engine of economic growth. They are at the heart of developing countries' entrepreneurship, the source of most new employment and productive investment, and the basis for growth and poverty reduction. Despite the economic potential of SMEs, they face severe constraints related to access to resources, finance, and services, as well as procedural barriers all of which limit their potential to invest, innovate, and improve productivity and sustainability. To address these constraints, International Finance Corporation (IFC) developed the SME Solutions Centre (SSC) Pilot Program in Kenya. The SSC value proposition centers on four key pillars: access to finance, access to advisory services/technical assistance (now SME management solutions), access to reliable market information, and support for an enhanced business enabling environment. This smart lesson details the lessons learned from the SSC's experience with the access to finance pillar.